A STUDY ON COMPARATIVE ADVERTISING IN INDIA - Rupa Khanna Malhotra (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
A comparative advertisement is one in which a certain product directly mentions a rival by name with the intention of demonstrating how inferior the rival is to the product identifying it. It is a marketing tactic in which a corporation presents its goods or services as superior to those of a rival. A side-by-side comparison of the features of a company's products and those of a rival company's products may be printed as part of a comparative advertising campaign. It might also include a cost-versus-value comparison. A promotional method known as comparative advertising involves the firm's advertising message making explicit or implicit comparisons to rival brands. Comparative advertising has matured and is projected to become more and more significant as a marketing tactic in India for both consumer durable and non-durable goods. The current research is a modest attempt to investigate importance, advantage, and disadvantage before assessing the effectiveness of communication based on an empirical strategy. Comparative advertising is when one party promotes its products or services by making comparisons to those of another party. This other party is frequently his rival or the company that dominates the market for that commodity or service. In order to increase the advertiser's sales, a comparison is made between the two products, either by implying that the advertiser's product is of equal or superior quality to the compared one, or by disparaging the compared product's quality. This article attempts to address the idea of comparative advertising within the context of intellectual property law by examining the various factors involved, statutory enactments, positions taken by courts of law in India and abroad, honest and unfair practices associated with CA, and finally, a comparative analysis of laws of other countries, thereby highlighting the ambiguity and lack of comprehensive laws in India.